Pretreatment with G-CSF Could Enhance the Antifibrotic Effect of BM-MSCs on Pulmonary Fibrosis - Feiyan Zhao; Wei Liu; Shaojie Yue; Lei Yang; Qingzhong Hua; Yan Zhou; Haipeng Cheng; Ziqiang Luo; Siyuan Tang (Stem Cells International)
Granulocyte colony-stimulating factor (G-CSF) can promote the repair of a variety of damaged tissues, but the underlying mechanisms have not yet been fully elucidated. Bone marrow mesenchymal stem cells (BM-MSCs) play an important role in the repair of damaged tissue. The aim of this study was to explore whether pretreating BM-MSCs with G-CSF can promote their ability of homing to the lung after in vitro transplantation via upregulating the CXCR4 expression, potentially markedly increasing the antifibrotic effect of BM-MSCs. The BM-MSCs pretreated with G-CSF were transplanted into a mouse on day 14 after bleomycin injection. The antifibrotic effects of BM-MSCs in mice were tested on day 21 by using pathological examination and collagen content assay. Pretreatment of BM-MSCs with G-CSF significantly promoted their ability of homing to the lung and enhanced their antifibrotic effects. However, knocking down the CXCR4 expression in BM-MSCs significantly inhibited the ability of G-CSF to promote the migration and homing of BM-MSCs to the lung and the resulting antifibrotic effects. We also found that G-CSF significantly increased the CXCR4 expression and AKT phosphorylation in BM-MSCs, and the AKT pathway inhibitor LY294002 significantly diminished the ability of G-CSF to upregulate the CXCR4 expression in BM-MSCs. Pretreatment of BM-MSCs with G-CSF promotes the homing of BM-MSCs to the lung via upregulating the CXCR4 expression, leading to a marked increase in the antifibrotic effects of BM-MSCs. This study provides new avenues for the application of BM-MSCs in the repair of different tissues.